Inhibition of pyrimidine biosynthesis targets protein translation in acute myeloid leukemia - Joan So; Alexander C Lewis; Lorey K Smith; Kym Stanley; Rheana Franich; David Yoannidis; Lizzy Pijpers; Pilar Dominguez; Simon J Hogg; Stephin J Vervoort; Fiona C Brown; Ricky W Johnstone; et al. (EMBO Molecular Medicine)
Abstract The mitochondrial enzyme dihydroorotate dehydrogenase (DHODH) catalyzes one of the rate‐limiting steps in de novo pyrimidine biosynthesis, a pathway that provides essential metabolic precursors for nucleic acids, glycoproteins, and phospholipids. DHODH inhibitors (DHODHi) are clinically used for autoimmune diseases and are emerging as a novel class of anticancer agents, especially in acute myeloid leukemia (AML) where pyrimidine starvation was recently shown to reverse the characteristic differentiation block in AML cells. Herein, we show that DHODH blockade rapidly shuts down protein translation in leukemic stem cells (LSCs) and has potent and selective activity against multiple AML subtypes. Moreover, we find that ablation of CDK5, a gene that is recurrently deleted in AML and related disorders, increases the sensitivity of AML cells to DHODHi. Our studies provide important molecular insights and identify a potential biomarker for an emerging strategy to target AML.